HYPOGLYCAEMIC EFFECT OF LEAF DECOCTION OF PANASA [ARTOCARPUS HETEROPHYLLUS LAM] IN TYPE II DIABETES MELLITUS- A CLINICAL STUDY - G.N, *Sree Deepthi; Eapen, Jollykutty; C.B, Roopesh Kumar (International Journal of Ayurveda and Pharma Research, 2017)
Panasa (Artocarpus hetrophyllus Lam.), the well known jackfruit tree, is a tree with wide ethnomedicinal uses. It is a drug used by the traditional Ayurveda physicians of Kerala for the treatment of diabetes mellitus. Hypoglycaemic effect of leaves of Artocarpus hetrophyllus Lam. is experimentally proven through in vitro and in vivo studies. Estimates shows that by the year 2025, the number of people suffering from diabetes in the world will be 350 million, of which 70 million will be in India. As diabetic patients have to take lifelong medication the medicines chosen should be safe, cost effective and free from side effects. So it is the need of the hour to find out a safer and cost effective medicine for diabetes. The present study is on the hypoglycemic effect of leaf decoction of Panasa (Atrocarpus hetrophyllus Lam.) in type 2 diabetic patients. The clinical trial was undertaken as a before and after trial with 30 patients for a period of 30 days. The trial drug showed a highly significant effect in reducing the Fasting Blood Sugar (FBS, P<0.001), Post Prandial Blood Sugar (PPBS, P=0.001) & total cholesterol (P<0.001). Also it showed a significant role in relieving associated symptoms like Polyuria, polyphagia, Polydipsia, lassitude, joint pain, excessive sweating and dryness of mouth. This study throws light into the scope of Artocarpus heterophyllus Lam in future researches as it is a drug available in various parts of the world, which is cost effective and proven to be safe for diabetes mellitus.